Antibiotics influence the risk of anti-drug antibody formation during anti-TNF therapy in Chinese inflammatory bowel disease patients - Sun, Meng; Ju, Jingyi; Xu, Hongzhen; Luo, Mengqi; Li, Zhaoyang; Wang, Yufang (Frontiers in Pharmacology, 2024)
Aims: The formation of anti-drug antibodies (ADAs) during anti-tumor necrosis factor (anti-TNF) therapy is reported to lead to reducing serum drug levels, which may bring about a loss of response to treatment. Previous research has suggested an association between specific antibiotic classes and ADA formation during anti-TNF therapy. However, there are few studies specifically examining this association in Chinese inflammatory bowel disease (IBD) patients. Therefore, our study aimed to evaluate the possible effect of antibiotic use on ADA formation to anti-TNF therapy in Chinese patients with IBD. Methods: A total of 166 patients with IBD, including 149 with Crohn’s disease (CD) and 17 with ulcerative colitis (UC), were included in this retrospective analysis. These patients were initially treated with anti-TNF therapy (infliximab or adalimumab) after January 2018 and reviewed with available ADA levels before October 2023. After univariable analysis of all the variables, a multivariate Cox proportional hazards model was used to assess the association between antibiotic use and ADA development. Results: Among 166 IBD patients treated with infliximab (108/166, 65.1%) or adalimumab (58/166, 34.9%), 31 patients (18.7%) were measured as positive ADA levels. Cox proportional hazard model demonstrated an increased risk of ADA formation in IBD patients who used β-lactamase inhibitors (HR=5.143, 95%CI 1.136-23.270, p=0.033), or nitroimidazoles (HR=4.635, 95%CI 1.641-13.089, p=0.004) during 12 months before the ADA test. On the contrary, a reduced risk was noted in patients treated with fluoroquinolones (HR=0.258, 95% CI 0.072-0.924, p=0.037). Moreover, the median serum infliximab or adalimumab concentration in patients with positive ADA levels was significantly lower than that in patients with negative ADA levels (infliximab: 0.30 vs. 1.85 μg/ml, p<0.0001; adalimumab: 0.45 vs. 7.55 μg/ml, p=0.0121). Conclusion: ADA development is associated with various antibiotic classes. β-lactamase inhibitors and nitroimidazoles might increase the risk of ADA formation during anti-TNF therapy in Chinese IBD patients, while the treatment with fluoroquinolones could probably reduce such risk. There were certain limitations in the retrospective analysis of the study, therefore, the results are just for reference, and other studies are needed to further confirm our findings.